Knowledge and attitude regarding periodontal disease leading to adverse pregnancy outcomes among accredited social health activist workers in Davanagere Taluk: a cross-sectional survey - Yavagal, Puja C.; D. J., Veeresh; Lawrence, Denzy; Jogendranath Sosale, Likitha; Hadalgi, Prasad P.; Sreehari, Rakshith (International Journal Of Community Medicine And Public Health, 2024)
Background: Periodontal disease is linked to adverse pregnancy outcomes. A study was done to assess knowledge and attitude regarding periodontal disease leading to adverse pregnancy outcomes among Accredited Social Health Activist (ASHA) workers in Davanagere Taluk. Methods: A cross-sectional survey was done involving 280 ASHA workers of Davanagere taluk in a field setting. Data regarding demographic details and knowledge and attitude related to periodontal disease leading to adverse pregnancy outcomes was collected from research participants using a questionnaire which was tested for validity and reliability. Responses were presented in percentages and Pearson’s correlation test was used for data analysis. Results: Majority of ASHA workers (50-54%) felt that pregnancy and its outcomes were not related to gum disease and 15-20% of them did not know about it. Around 75-88% felt that pregnancy related outcomes like preterm birth, low birthweight baby, gestational diabetes were not linked to periodontal disease. Very few felt (11-21%) that gum disease was linked to adverse pregnancy outcomes. There was no significant correlation (p>0.05) between knowledge scores and age, educational level and years of work experience of ASHA workers. Conclusions: Knowledge and attitude regarding periodontal disease leading to adverse pregnancy outcomes among Accredited Social Health Activist workers in Davanagere Taluk was poor.